Aplikasi Pestisida Nabati Larutan Kemangi Terhadap Hama Penghisap Daun Cabai - Marisa Thaibah; Helda Orbani Rosa; M Indar Pramudi (JURNAL PROTEKSI TANAMAN TROPIKA, 2021)
This research was carried out with the aim of knowing the effect of the application of basil solution on chili leaf-sucking pests (whitefly, thrips and aphids) which was carried out in the garden of the Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru for 5 months from December 2020 to May 2021. The research method used a randomized design. Complete (CRD) with 4 treatments of concentration of basil solution and 2 controls (without treatment and chemistry) with observation parameters in the form of abundance of leaf-sucking pests, seriousness of pest attacks on plants and indications of virus attack events. Each treatment was repeated 4 times to create 24 experimental units. Each treatment consisted of 4 polybags. Each polybag is planted with 1 plant so that the total number of plants is 4 samples. In total there are 96 plants. The lowest seriousness of the attack occurred in the TKC and TKD treatments, whereas the lowest population abundance was in the TKA and TKB treatments. From the results, it can be concluded that the use of basil leaf solution can reduce the attack of leaf-sucking pests on chili.